2016
DOI: 10.2459/jcm.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal pro-B-type natriuretic peptide-guided therapy in patients hospitalized for acute heart failure

Abstract: NT-proBNP-guided therapy resulted mainly in an increase of diuretics in acute setting and compared with clinical evaluation alone did not improve prognosis. However, the reduction of NT-proBNP at discharge was an independent predictor of outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Fourteen out of 18 medical therapy trials presented data on change in NP levels during the trial (Anguita et al 2010;Carubelli et al 2016;Eurlings et al 2010;Felker et al 2017;Januzzi et al 2011;Jourdain et al 2007;Karlstrom et al 2011;Lainchbury et al 2009;Maeder et al 2013;Murdoch et al 1999;Persson et al 2010;Pfisterer et al 2009;Schou et al 2013;Shah et al 2011;Stienen et al 2018;Troughton et al 2000), of which 7 out of 14 trials presented data on NP levels within the first 6 months of the trial (Anguita et al 2010;Carubelli et al 2016;Felker et al 2017;Maeder et al 2013;Pfisterer et al 2009;Shah et al 2011;Stienen et al 2018). Three trials Shah, Carubelli, and Stienen were excluded as the data was reported at differing time points before 6 months: Stienen (mean 12 ± 10 days) (Stienen et al 2018), Carubelli (mean 11 ± 9 days) (Carubelli et al 2016) and Shah (4 months) (Shah et al 2011). The overall point estimate of the four remaining trials was nonsignificant at 6 months of NP-directed medical therapy with low heterogeneity in the included trials (Fig.…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fourteen out of 18 medical therapy trials presented data on change in NP levels during the trial (Anguita et al 2010;Carubelli et al 2016;Eurlings et al 2010;Felker et al 2017;Januzzi et al 2011;Jourdain et al 2007;Karlstrom et al 2011;Lainchbury et al 2009;Maeder et al 2013;Murdoch et al 1999;Persson et al 2010;Pfisterer et al 2009;Schou et al 2013;Shah et al 2011;Stienen et al 2018;Troughton et al 2000), of which 7 out of 14 trials presented data on NP levels within the first 6 months of the trial (Anguita et al 2010;Carubelli et al 2016;Felker et al 2017;Maeder et al 2013;Pfisterer et al 2009;Shah et al 2011;Stienen et al 2018). Three trials Shah, Carubelli, and Stienen were excluded as the data was reported at differing time points before 6 months: Stienen (mean 12 ± 10 days) (Stienen et al 2018), Carubelli (mean 11 ± 9 days) (Carubelli et al 2016) and Shah (4 months) (Shah et al 2011). The overall point estimate of the four remaining trials was nonsignificant at 6 months of NP-directed medical therapy with low heterogeneity in the included trials (Fig.…”
Section: Results Of Individual Studies and Synthesis Of Resultsmentioning
confidence: 99%
“…Most patients were randomized once heart Karlstrom et al 2011;Murdoch et al 1999;Ozkara et al 2007;Persson et al 2010;Schou et al 2013;Shah et al 2011;Stienen et al 2018;Troughton et al 2000). The remainder of the trials combined patients with preserved and reduced ejection fraction (Anguita et al 2010;Berger et al 2010;Carubelli et al 2016;Eurlings et al 2010;Lainchbury et al 2009;Maeder et al 2013;Pfisterer et al 2009). The conduct of the trial intervention arms is shown in Table 2.…”
Section: Study Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that reductions in BNP between admission and discharge predict better outcomes, whether defined by an absolute or relative reduction, with common thresholds being absolute reduction of 250 pg/mL in BNP or 30% reduction in either BNP or NT-proBNP. 11,12 The PRIMA II study (NT-proBNP Target on the Reduction of Readmission and Mortality Rates) in this issue of Circulation provides new information about the changes in natriuretic peptides during effective therapy of patients hospitalized with heart failure.…”
Section: Titration Strategies Guided By Natriuretic Peptide Levelsmentioning
confidence: 99%